ASSESSMENT OF THE CORRELATION BETWEEN COVID-19 PNEUMONIA SEVERITY AND PULMONARY ARTERY DIAMETER MEASUREMENT WITH COMPUTED TOMOGRAPHY SCAN - RANI, SHUBHANSHI; SAH, NIRAJ KUMAR; KUMAR, RAUSHAN; BOORA, NAVREET (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This consideration used the computed tomography scan to investigate and evaluate relationship between COVID-19 pneumonia severity and pulmonary artery diameter, ascending aorta diameter (AAD), right and left pulmonary artery diameter (LPAD), and ratio of main pulmonary artery diameter (MPAD) to AAD in COVID-19 patients. Methods: This retrospective and cross-sectional consideration was done on 90 confirmed COVID-19 patients. Diameter of MPAD, AAD, LPAD, and right pulmonary artery diameter was calculated on a solitary transverse section designated at extent of main pulmonic arterial trunk separation. Ratio of MPAD TO AAD was calculated by division of the values of MPAD and AAD in manual mode. Result: In this retrospective consideration, population was divided into groups of mild (43 patients with 42.6% males), moderate (30 patients with 36% males), and severe (17 patients with 21.3% males) pneumonia patients. Diameter of MPA in mild COVID pneumonia group had 23.8±3.4, moderate group had 26.7±4.3, and severe group had 29.9±3.6 (p<0.001). Diameter of AA in mild group had 28.1±3.7, moderate group had 31.0±4.2, and severe group had 34.0±4.2 (p < 0.001). Diameter of LPA in mild group had 16.1±2.0, moderate group had 17.5±2.1, and severe group had 19.1±2.0 (p < 0.001). Conclusion: Pneumonia severity of COVID-19 patients in severe group showed greater MPAD as compared to moderate group and then mild group patients, respectively. A chest computed tomography (CT) scan/high-resolution CT can be useful to determine the pneumonia extension evaluation, by measuring the MPAD which can provide extraprognostic information and aid doctors inpatient treatment.